A COMPARISON OF VISUAL OBSERVATIONS OF SURFACE OIL WITH SYNTHETIC APERTURE RADAR IMAGERY OF THE SEA EMPRESS OIL SPILL - Jones B. (My University, 2001)
A comparison has been made between the visual observations of surface oil and four satellite-borne Synthetic Aperture Radar (SAR) images taken during the Sea Empress oil spill in February 1996. Whilst the basic oil slick imaging capabilities of SAR are well documented, to be of use at the time of a major oil spill, the imagery must be able to provide information on the thickness of oil. This analysis suggests that, under certain environmental conditions, this is possible. The optimum wind speed for the identi cation of heavy surface oil is around 5–6 m sÕ 1 . At this wind speed, light and medium sheen is not evident in the imagery and there is a distinction between the backscatter reductions due to heavy sheen and thick brown/black oil. At higher wind speeds, even thick oil slicks readily mix into the water column and their SAR signature weakens. In light winds, pattern recognition is very important to the identi cation of oil slicks. The images are more sensitive to the presence of sheen within the sheltered waters of Milford Haven than in the open coastal waters, indicating a possible relation-ship between sheen visibility in satellite-borne SAR and sea state.